The Muses' Concord Literature, Music, and the Visual Arts in the Baroque Age - Jensen, H. James (Indiana University Press, 1976)
The glories of the Baroque age, mainly the arts of literature, painting, and music, areewpoint notable for its scope and catholicity. The term Baroque here denotes a period from the early seventeenth to try. From Jensen's method of moving from one country and time to another we discover that Addison's writings, Vivaldi'gs, Shaftesbury's aesthetics, and Coeffeteau's psychology all help elucidate seventeenth-century ideas and works of ajor attention to Enland, but does not neglect France and Italy. Ranging widely over an entire aesthetic movement, he rtistic creation, rhetoric, education, moral values, social mores, scientific discoveries, and issues of taste, and riation of Baroque art.